Skin-mates or neighbors? A seasonal study of amphibian chytrid and dermocystid infection in Boana pulchella (Anura: Hylidae) - Borteiro, Claudio (2018)
We studied in this work the prevalence of two eukaryotic skin pathogens in a population of the frog Boana pulchella (Anura, Hylidae) from southeastern Uruguay, the fungus Batrachochytrium dendrobatidis (Rhizophydiales) and the protoctistan Valentines rwandae (Ichthyosporea, Dermocystida), between 2012 and 2014. In both cases higher prevalences were recorded in cooler seasons, winter and early spring for B. dendrobatidis (0.78 and 0.95 respectively) and autumn for V. rwandae (0.33 and 0.49), with mean temperatures between 11.5 and 17.8°C. No cases of infection were detected in summer. In both cases the probability of infection was strongly influenced by season (and also the year for B. dendrobatidis), but in neither case the occurrence of the other pathogen was significant. The parasitic cycles seem to occur independently and are likely strongly associated to environmental temperatures. Future field studies on amphibian eukaryotic pathogens from temperate areas of South America should consider seasonal variations.